2020
DOI: 10.3389/fpubh.2020.00431
|View full text |Cite
|
Sign up to set email alerts
|

Potential Cost-Savings From the Use of the Biosimilars in Slovakia

Abstract: Objectives: To analyse the market shares of biosimilars in Slovakia and to calculate the potential cost-savings from the use of biosimilars in Slovakia based on two different data sources. Methods: National reimbursement lists from the Czech Republic, Hungary, Poland and Slovakia were used for analyzing the availability of biosimilars with public funding. In addition, the reimbursement dossiers of biosimilars, the justifications of reimbursement decisions by the Slovak Ministry of Health, and final reimburseme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Table 3 contains details of a number of activities by health authorities across Europe to enhance the prescribing of biosimilars and their impact. In addition, Tesar et al (2020) recently calculated that the health fund in Slovakia could have saved an estimated €35 to 50 million per year if biosimilars with marketing authorisations had been readily available and promoted [240], and such savings are likely to grow. It is imperative though that patients are involved in any switching programme to help negate any potential nocebo effect as well as provide feedback regarding any concerns with the effectiveness and safety of the biosimilars [235,241].…”
Section: Biosimilarsmentioning
confidence: 99%
“…Table 3 contains details of a number of activities by health authorities across Europe to enhance the prescribing of biosimilars and their impact. In addition, Tesar et al (2020) recently calculated that the health fund in Slovakia could have saved an estimated €35 to 50 million per year if biosimilars with marketing authorisations had been readily available and promoted [240], and such savings are likely to grow. It is imperative though that patients are involved in any switching programme to help negate any potential nocebo effect as well as provide feedback regarding any concerns with the effectiveness and safety of the biosimilars [235,241].…”
Section: Biosimilarsmentioning
confidence: 99%
“…Therefore, variations can be seen in the availability of biosimilars across Europe ( Kawalec et al, 2017 ). From 2016 to the middle of 2018, not a single biosimilar became available in Slovakia; in this respect, Slovakia lagged behind other V4 and other EU countries ( Tesar et al, 2020 ). This trend changed during the second half of 2018, in which six other biosimilars were reimbursed in Slovakia.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has also shown that Slovakia is one of the states within the European Union that has significant potential to improve health outcomes without increasing financial resources ( Kuenzel and Solanic, 2018 ). Therefore, it is important that we implement reimbursement practices for off-patent medicines that maximize the social benefits of generic and biosimilar medicines for patients in Slovakia ( Tesar et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Following the recent patent expiration of originator etanercept, the more affordable biosimilar versions of etanercept are available. Switching patients from originator etanercept to its biosimilars as part of routine clinical practice may result in significant public and private drug cost savings [ 5 , 6 ]. The biosimilar products Brenzys and Erelzi were approved by Health Canada in August 2016 and April 2017 respectively [ 7 ].…”
Section: Introductionmentioning
confidence: 99%